Difference in biofilm formation between carbapenem-resistant and carbapenem-sensitive Klebsiella pneumoniae based on analysis of mrkH distribution. (March 2021) - Fang, Renchi; Liu, Haiyang; Zhang, Xiucai; Dong, Guofeng; Li, Jiahui; Tian, Xuebin; Wu, Zhenghai; Zhou, Jiancang; Cao, Jianming; Zhou, Tieli
Abstract: Object: To analyze the difference in biofilm formation between carbapenem-resistant and carbapenem-sensitive Klebsiella pneumoniae based on analysis of mrkH distribution and to further explore the function of mrkH for biofilm formation from the perspective of gene regulation. Methods: 40 imipenem-resistant strains and 40 imipenem-sensitive strains were selected to conduct experiments. Carbapenem (imipenem) susceptibility test was performed by the agar-dilution method. bla KPC resistance gene, type 3 fimbriae-related coding genes ( mrkA and mrkD ) and regulation gene ( mrkH ) were screened by PCR. Biofilm formation assay was performed using crystal violet staining method in MHB. The relative expression of genes that critically involved in biofilm formation ( mrkA, luxS, pgaA ) and carbapenem resistance ( ompk35, ompk36, acrB ) were measured by quantitative real-time PCR (qRT-PCR). Furthermore, the mrkH cassette was cloned into pGEM-T Easy plasmid to yield pGEM: pmrkH and expressed in Escherichia coli DH5α and K. pneumoniae FK1911, and the biofilm formation assay after transformation was further tested. Results: The MICs of imipenem were all more than 16 μg/mL in 40 imipenem-resistant strains and ranged from 0.125 μg/mL to 0.5 μg/mL in 40 imipenem-sensitive strains. Moreover, the bla KPC was identified in the 40 imipenem-resistant K. pneumoniae strains. All 80 K. pneumoniae strains were found to carry mrkA and mrkD genes. Interestingly, the mrkH gene was detected in 43 strains, of which 32 were carbapenem-sensitive strains. The biofilm formation capacity of strains carried mrkH cassette was significantly higher than other 37 strains in MHB media. The relative expression of mrkA in K. pneumoniae carrying mrkH gene was significantly up-regulated. Importantly, the biofilm formation ability of FK1911-pGEM: pmrkH strain was more higher than the strain of FK1911 in MHB medium. Conclusions: Our data demonstrated that MrkH played a crucial role in the regulation of biofilm formation by K. pneumoniae . In contrast to carbapenem-sensitive K. pneumoniae, carbapenem-resistant K. pneumoniae was less likely to have strong biofilm-forming capacity because it does not carry the mrkH gene. Highlights: Carbapenem-resistant K. pneumoniae was less likely to form strong biofilm. mrkH gene plays an important role in regulating biofilm formation. Difference in distribution of mrKH between carbapenem-resistant and -sensitive strains.